PERAN KEBIJAKAN PEMERINTAH TERHADAP PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL DI ERA DIGITALISASI BISNIS - Febianto, Krismon (Universitas Labuhanbatu, 2025)
The protection of Intellectual Property Rights (IPR) in the era of digitalization poses significant challenges, particularly with the rise of violations and piracy. This study aims to analyze the role of the Indonesian government's policies in protecting IPR and evaluate the effectiveness of existing policies. The research method employed is normative legal research with a statutory approach, utilizing document studies related to regulations and legal theories. The findings reveal a gap between regulations and their implementation in practice, as well as a lack of awareness among business actors, particularly Small and Medium Enterprises (SMEs), regarding the importance of IPR protection. There is a need for regulatory updates, enhanced law enforcement capacity, and education for business actors to ensure that IPR protection in the digital era can be more effective.Keywords: Intellectual Property Rights; Business; Digitalization